Factors associated with vocal problems in teachers from Montes Claros, Minas Gerais - Rodrigues Souza de Campos, Ana Grazielle; Teodora de Oliveira, Layla; de Sousa Medeiros, Daniel; Alves Pereira, Samuyara Alexandra; Rossi Barbosa-Medeiros, Mirna; Rossi-Barbosa, Luiza Augusta Rosa (O Mundo da Saúde, 2022)
Teachers use their voices as a work tool and end up exposing themselves to risks of overload and vocal effort, which may impair professional performance. This study aimed to verify the prevalence and factors associated with vocal problems in teachers during the COVID-19 pandemic. This is a cross-sectional, analytical study, formed by 82 elementary school teachers from three state schools in Montes Claros, Minas Gerais, Brazil. To assess vocal problems, the Screening Index for Voice Disorder - SIVD was used. Data collection was carried out in July and August 2020, using the Google Forms Platform. A bivariate analysis was performed, followed by Poisson regression at a 5% significance level. The prevalence of vocal problems was 42.7% (n=35) and of possible vocal disorders was 11.0% (n=9). The most reported symptoms were phlegm (25.6%), hoarseness (19.5%), strained speech (17.1%), and dry throat (15.9%). In the final analysis of vocal problems, the diagnosis of gastroesophageal reflux (PR=2.245; 95%CI=1.548-3.256) and depressive symptoms (PR=1.722; 95%CI=1.020-1.907) were associated. The shift to remote classes showed the need for guidance for healthy vocal quality.